Co-operative learning, psychometric adaptation, and invariability of the academic satisfaction scale in Spanish university students - Robles-Bello, María Auxiliadora; Sánchez-Teruel, David; Gavin Chocano, Óscar; González Luque, Alfonso; Camacho Conde, José Antonio (Frontiers in Psychology, 2022)
It is necessary to understand the measurement of academic satisfaction in a variety of cross-cultural contexts. The first aim was to evaluate the psychometric properties of the Lent et al. (2005) academic satisfaction scale, to explore its structural validity, to assess its differential item function, including gender and age invariance in university students. Study 2 aimed to assess whether academic satisfaction improved after the application of a teaching instructional approach based on cooperative learning, while a cross-sectional study was performed in several stages. Descriptive, confirmatory, and scale reliability analyses were carried out with indices for goodness-of-fit, such that a new scale was obtained with a single-factor structure. A reduction to 6-items in this sample exhibited better psychometric properties. Configural invariance by gender and age indicated that men and women had a similar understanding of the new scale. Given significant differences between groups, the cooperative learning group scored higher in academic satisfaction.